ETHICS BETWEEN REASON AND SHARIA: “A COMPARATIVE CRITICAL STUDY” - Mustafa, Ali; Salih, Amad (Humanities Journal of University of Zakho, 2024)
The research revolves around the importance of the mind in the statement of moral values, and if it can play a role in this field, the research mentioned the Islamic intellectual trends in this field, which revolved around two main trends, a section that governs that the qualities of good and ugliness are subjective in actions, and in the ability of the mind to see them and know the rule of God in them before the mission of the prophets, and a team of them went to the order of blame for it sooner and later before the advent of Sharia. The other part believed in a kind of moral consequences that could be defined by reason based on the interest and corruption decided by the mind, but they remain additional qualities of consideration, and do not acquire their value and do not outweigh one over the other until after the divine command is received. The first team is headed by the Mu’tazilites, while the second is led by the Ash’aris. And the most famous division of the subject of dispute - although it was considered - what Imam Razi mentioned, he mentioned a division of three aspects, what was in accordance with the nature and purpose and what was contrary to it, and the latter was the characteristic of perfection and the recipe of deficiency, and the third what deserved praise and slander. So they unanimously agreed on the rationality of the first two and differed in the third, so the Mu’tazila and those who agreed with them went to make it mental as well, and the Ash’aris disagreed with them and those who agreed with them that Sharia is the one that gives the quality of good and ugliness to it. They are not subjective, and the mind cannot be certain of God’s judgment in them before the law. The research mentioned the evidence of the two groups with discussion and analysis, and the weighting of the subjectivity of the qualities of good and ugliness in the acts in the absent and the witness, and the possibility of the mind to stand on it, with the denial of blame before the arrival of Sharia for the frankness of the legal texts in that the reward and punishment are arranged after the arrival of the message and proof of the argument.